Monitoring children’s health in a public daycare center: focus on their nutritional profile - Santos, Nathanielly Cristina Carvalho de Brito; Pinto, Maria Benegelania; Henriques, Amanda Haissa Barros; Cavalcanti, Joseane da Rocha Dantas; Brito, Cristhianne Carvalho de; Reichert, Altamira Pereira da Silva (Rev Rene, 2013)
One aimed to identify the nutritional profile of children in a public daycare center in the city of Cuité-Paraíba, from the perspective of health surveillance. This is a cross-sectional, exploratory-descriptive, field study with a quantitative approach, performed in 2011, with 55 children from 6 to 60 months of life, assisted full time in a public daycare center, who met the selection criteria: be attending the daycare center; and not present any disability. One used for evaluation the anthropometric measurements of weight, height and Body Mass Index, according to the growth curve suggested by the Ministry of Health. One identified that 96.4% had adequate nutritional status, however, 7.3% had overweight risk and 3.6% underweight risk, especially girls. It is important to raise managers’, professionals’ and parents’ awareness about the health surveillance of children in daycare centers for identification and intervention against nutritional changes, encouraging an adequate child growth.DOI:https://doi.org/10.15253/2175-6783.2013000400006